The use of torus palatinus in the identification of unknown skeletal remains. (September 2019) - Gupta, Avneesh; Rizor, Leann; Saul, Julie; Kesha, Kilak; Berman, Gary
Torus palatinus (TP) is a benign, bony outgrowth located on the hard palate. Variation in this trait occurs, ranging from absent to a protuberance several millimeters in length. If a TP becomes too large, it can interfere with daily activities and thus warrant medical attention. This case utilised the unique morphology of a TP after surgical invention to identify the unknown skeletal remains of a woman missing for six years. Even though there is still much unknown regarding the aetiology, occurrence and prevalence of TP, this study demonstrates the usefulness of anatomical variants in the identification of unknown skeletal remains.